Major, Minor and Trace Elements Existence in Surface Sediments from Gwadar to Jiwani Coastal Areas of Pakistan : Major, Minor and Trace Elements Existence in Surface Sediments from Gwadar to Jiwani Coastal Areas of Pakistan - Waseem Haider, Syed; Mahmood, Tariq; Siddiqui, Saima (International Journal of Economic and Environmental Geology, 2024)
This study was carried out along the western coastal parts of Balochistan from Gwadar east Bay to Jiwani. The local anomaly of major, minor and trace elements were studied in this area. Zone-I (Gwadar east and west Bay) indicates that calcium oxide, potassium oxide and titanium dioxide have higher or average concentrations, while Zone[1]II indicates higher or average concentrations of calcium oxide, titanium dioxide and ferric oxide. Trace elements zirconium, chromium, europium, strontium, and copper are in higher or average concentrations in both zones. Gwadar west Bay and Jiwani are intermediate in carbonate, which show a high degree of maturity, suggesting the high rate of weathering in the source area. Sediment samples from Ganz, Jiwani, and Gwadar east Bay represent the quartz-rich fields in this region. Gwadar east Bay has a positive correlation between aluminium oxide and potassium oxide which suggests that abundance of potassium oxide is controlled by variation in K-feldspar contents. A positive correlation between strontium and calcium oxide suggests that strontium is associated with calcium oxide in biogenic carbonate material in Gwadar west Bay. The positive correlation between aluminium oxide, copper, and zinc in Pishukan indicates that the abundance of these elements is due to limited silt and clay fractions present in sediments. Enrichment factor shows that chromium and strontium are probably of anthropogenic origin in this region.